Neuron Density and Serotonin Receptor Binding in Prefrontal Cortex in Suicide - Underwood, Mark D. (2011)
Although serotonin receptor and cytoarchitectonic alterations are reported in prefrontal cortex (PFC) in suicide and depression, no study has considered binding relative to neuron density. Therefore, we measured neuron density and SERT, 5-HT(1A) and 5-HT(2A) binding in matched suicides and controls. Suicides and normal controls (N=15 matched pairs) were psychiatrically characterized. Neuron density and binding were determined in dorsal (BA9) and ventral (BA47) PFC by stereology and quantitative autoradiography in near-adjacent sections. Binding index was defined as the ratio of receptor binding to neuron density. Suicides had lower neuron density in the gyrus of both areas. The binding index was lower for the serotonin transporter in BA47 but not in BA9; the 5-HT(1A) binding index was higher in BA9 but not in BA47, while the 5-HT(2A) binding index was not different between groups. SERT binding was lower in suicides in BA47 but not BA9, while 5-HT(1A) binding was higher in BA9 but not BA47. SERT binding negatively correlated with 5-HT(1A) binding in BA47 in suicides. Neuron density decreased with age. 5-HT(1A) binding index was higher in females than males. We found lower neuron density and lower SERT binding index in both PFC regions in suicides. More 5-HT(1A) binding with less SERT binding and the negative correlation in depressed suicides suggests post-synaptic receptor upregulation, and it is independent of the difference in neuron density. Thus, abnormalities in both cortical neurons and in their serotonergic innervation are present in suicides and future studies need to determine whether cortical changes reflect the trophic effect of altered serotonin innervation.